The political economy of a plural world : critical reflections on power, morals and civilization - Cox, Robert W., 1926-2018 (Routledge/RIPE series in global political economy. RIPE series in global political economy., 2003)
This book addresses such core issues as global civil society, power and knowledge, the covert world, multilateralism, and civilizations and world order. It is essential reading for all students and academics in the field.